The Effect of Athlete Mindfulness on the Development of Athlete Psychological Skills - Aydanur Önal; Nuh Osman Yıldız; Zülbiye Kaçay (Türk Spor ve Egzersiz Dergisi)
The aim of this study was to investigate the effect of athlete mindfulness, which is expressed as the ability of athletes to establish a cause-effect relationship without losing the perception of reality in the moments and situations related to sports, on the development of their psychological skills, which is emphasized by sports psychologists to positively affect athlete performance by 85%. This study was designed according to the relational screening and causal comparison methods in order to examine the interaction between the variables. The study group comprised of 362 athletes who can be reached by non-random sampling methods and determined according to the criterion sampling method. As a data collection tool "Athlete Psychological Skills Assessment Scale" developed by Smith et al., (1995) and adapted to Turkish culture by Erhan et al. (2015) was used. Also, “Athlete Mindfulness Scale” developed by Thienot et al. (2014) and adapted to Turkish culture by Tingaz (2020) was used. In the analysis of the data obtained, the demographic variables of the participants were analyzed by correlation and t-test in independent samples, and structural equation model was used in determining the effect of mindfulness levels of athletes on the development of their psychological skills. As a result, it has been concluded that the mindfulness of the athletes is a significant predictor of the development of the psychological skills of the athletes and explains it at the level of .30.